Dis/locating Imagined Futures: The disabled habitus and young disabled people in alternative provision - Johnston, Craig (People, Place and Policy Online, 2020)
This article considers the disabled habitus and a small group of young disabled people who are attending an Alternative Provision (AP), within one English Further Education College. The aim of this article is to understand the significance of the body in relation to these students’ work to assemble and locate a vivid imagined future, and proposes that the college functions as a critical space where much of this body work gets played-out. The article draws on an ethnographic study of a group of school-aged, working-class disabled students; a group whose educational, employment and social outcomes are chronically stagnant in England. The article postulates that their inclusions in to a college have unintended effects and consequences, which illuminates some of the pernicious consequences of school exclusion. Despite several negative experiences, both inside and outside the AP, the article shows how young disabled people develop and appropriate capital to inform and disrupt the habitus. The article concludes with questions about APs as constituting the means to confer value upon young disabled students in search of identities that are apposite to paid employment within the contemporary (and future) labour market.
Keywords: Education; alternative provision; capital; disability; habitus; young people